A donor splice site mutation in CISD2 generates multiple truncated, non-functional isoforms in Wolfram syndrome type 2 patients - Monica Cattaneo; Lucia La Sala; Maurizio Rondinelli; Edoardo Errichiello; Orsetta Zuffardi; Annibale Alessandro Puca; Stefano Genovese; Antonio Ceriello (BMC, 2017)
Abstract Background Mutations in the gene that encodes CDGSH iron sulfur domain 2 (CISD2) are causative of Wolfram syndrome type 2 (WFS2), a rare autosomal recessive neurodegenerative disorder mainly characterized by diabetes mellitus, optic atrophy, peptic ulcer bleeding and defective platelet aggregation. Four mutations in the CISD2 gene have been reported. Among these mutations, the homozygous c.103 + 1G > A substitution was identified in the donor splice site of intron 1 in two Italian sisters and was predicted to cause a exon 1 to be skipped. Methods Here, we employed molecular assays to characterize the c.103 + 1G > A mutation using the patient's peripheral blood mononuclear cells (PBMCs). 5'-RACE coupled with RT-PCR were used to analyse the effect of the c.103 + 1G > A mutation on mRNA splicing. Western blot analysis was used to analyse the consequences of the CISD2 mutation on the encoded protein. Results We demonstrated that the c.103 + 1G > A mutation functionally impaired mRNA splicing, producing multiple splice variants characterized by the whole or partial absence of exon 1, which introduced amino acid changes and a premature stop. The affected mRNAs resulted in either predicted targets for nonsense mRNA decay (NMD) or non-functional isoforms. Conclusions We concluded that the c.103 + 1G > A mutation resulted in the loss of functional CISD2 protein in the two Italian WFS2 patients.